Chemistry and Biology of Glycopeptides with Antibiotic Activity - Tan, Huilong; Guo, Hua; Wang, Shuailiang; Kong, Qidi; Li, Wenzheng; Zeng, Wenbin (Protein and Peptide Letters, 2014)
Glycopeptides with potent antibiotic activity are vital for the treatment of severe infections that caused by Gram-positive bacteria, especially methicillin-resistant Staphylococcus aureus. Recently, the glycopeptide-resistant Grampositive bacteria present a serious challenge to public health after more than decades of clinical use. Additionally, the antibacterial activity and side effect become an increasing crisis and should have to be taken into account. As a consequence, new glycopeptide antibiotics are needed to face with these problems. In the past years, with the development of natural product chemistry, more and more glycopeptide compounds with promising biological properties were discovered. In addition, the chemical modification of the known glycopeptide provides an opportunity for the discovery of new potential glycopeptide antibiotics. Considerable efforts have been made in this field in order to meet the clinical needs. In this article, we mainly focus on the advances of glycopeptide as antibiotics, including many representative glycopeptides or its analogues and derivatives. Taken together, we hope all this information is helpful for the discovery of new potential glycopeptide antibiotics.
Keywords: vancomycin